2011
DOI: 10.4317/medoral.16.e105
|View full text |Cite
|
Sign up to set email alerts
|

Intraorifice sealing ability of different materials in endodontically treated teeth

Abstract: Objectives: To evaluate Cavit™ G, ProRoot™ MTA and Tetric ® EvoFlow as intraorifice barriers to prevent coronal microleakage in root canal treatment. Study Design: Forty-two human single rooted teeth were divided randomly in three experimental groups of 10 specimens each and two control groups. The experimental groups were prepared with hand instrumentation and cold lateral condensed technique of the gutta-percha. Four millimetres of coronal gutta-percha were removed and replaced by one of the following fillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Pisano et al tested the coronal sealing ability of temporary filling materials to prevent microleakage of gutta-percha obturated root canals in human saliva and revealed that the IRM, Cavit, Super-EBA-filled orifice leaked less leakage than unsealed control group 40) . Another microleakage study 41) using glucose penetration model showed that Cavit, Tetric, and ProRoot MTA attained similar leakage values during the testing period when used as intraorifice barriers. As described above, previous researches support the importance of intraorifice barriers, but there is no consensus as to the protocols or materials used as the coronal barrier after root canal treatment except the thickness of the intraorifice barrier, which is recommended to be 3 to 4 mm 40,42,43) .…”
Section: Discussionmentioning
confidence: 97%
“…Pisano et al tested the coronal sealing ability of temporary filling materials to prevent microleakage of gutta-percha obturated root canals in human saliva and revealed that the IRM, Cavit, Super-EBA-filled orifice leaked less leakage than unsealed control group 40) . Another microleakage study 41) using glucose penetration model showed that Cavit, Tetric, and ProRoot MTA attained similar leakage values during the testing period when used as intraorifice barriers. As described above, previous researches support the importance of intraorifice barriers, but there is no consensus as to the protocols or materials used as the coronal barrier after root canal treatment except the thickness of the intraorifice barrier, which is recommended to be 3 to 4 mm 40,42,43) .…”
Section: Discussionmentioning
confidence: 97%
“…(6) Among the various sealing materials used to produce a coronal barrier, mineral trioxide aggregate (MTA) has gained much attention in recent years. (7)(8)(9)(10)(11)(12)(13)(14) The original formulation of MTA, developed at Loma Linda University, is manufactured by Dentsply International (ProRoot MTA and Tooth Colored MTA; Dentsply-Tulsa Dental, Tulsa-USA; Dentsply-Johnson City-USA) (15) . Other MTA types available are white and gray Angelus mineral trioxide aggregates (WAM-TA, GAMTA; Angelus, Londrina, PR, Brazil).…”
Section: Introductionmentioning
confidence: 99%
“…There are a limited number of studies investigating the coronal sealing ability of MTA and most of them compare the properties of 3 mm thick WMTA with other materials (7)(8)(9) . Two investigators evaluated the coronal sealing ability of 2 mm thick ProRoot MTA (10,11) , whereas others compared the coronal sealing ability of 4 mm thick ProRoot MTA with other materials (12,13) . Only, Jenkins et al (14) compared the sealing ability of 1, 2, 3, and 4 mm thicknesses of cavit, ProRoot MTA and tetric as intra-orifice barriers.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Coronal leakage has a negative influence on the prognosis of root canal treatment,[2] and plays a significant role in multirooted teeth, where accessory canals may be present in the furcation area. [3] Specifically, inflammatory changes can occur in the periodontal tissues because of a direct spread of microorganisms from the pulp chamber through these accessory canals.…”
Section: Introductionmentioning
confidence: 99%